The Diversion in Law Enforcement of Criminal Action of Children in the Judicial System of Children - Danang Sucahyo; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
Handling of crimes committed by children is carried out through the juvenile criminal justice system, as regulated in Act No. 11 of 2012. In Act No. 11 of 2012, the settlement of criminal cases of children is carried out by means of a diversion mechanism. This study aims to determine and examine diversion in law enforcement of child criminal acts in the juvenile criminal justice system. This study uses a normative juridical approach, which is descriptive analysis. The data used is secondary data obtained through library research, which is then analyzed qualitatively. The result of this research is that diversion is a persuasive action or an approach that aims to invite people to obey and enforce the law while still considering the sense of justice as a top priority in addition to providing opportunities for perpetrators to improve themselves. Diversion in the juvenile criminal justice process is regulated in Article 8 of Act No. 11 of 2012, which is carried out through deliberations involving the child and his/her parents/guardians, the victim and/or their parents/guardians, social advisers, and professional social workers. The diversion provision is applied to criminal offenses that carry a sentence of less than seven years and do not constitute a repetition of the crime. Diversion in the juvenile criminal justice process is regulated in Article 8 of Act No. 11 of 2012, which is carried out through deliberations involving the child and his/her parents/guardians, the victim and/or their parents/guardians, social advisers, and professional social workers. The diversion provision is applied to criminal offenses that carry a sentence of less than seven years and do not constitute a repetition of the crime. Diversion in the juvenile criminal justice process is regulated in Article 8 of Act No. 11 of 2012, which is carried out through deliberations involving the child and his/her parents/guardians, the victim and/or their parents/guardians, social advisers, and professional social workers. The diversion provision is applied to criminal offenses that carry a sentence of less than seven years and do not constitute a repetition of the crime.